2005
DOI: 10.1111/j.1748-0361.2005.tb00060.x
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence in Kentucky, Pennsylvania, and West Virginia: Disparities in Appalachia

Abstract: Cancer incidence in Appalachia was not found to be elevated. However, incidence of cancer of the lung/bronchus, colon, rectum, and cervix was elevated in Appalachia. The rates of unstaged cancer of every examined site were elevated in rural Appalachia, suggesting a lack of access to cancer health care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
123
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(134 citation statements)
references
References 29 publications
10
123
0
1
Order By: Relevance
“…However, elevated cancer mortality rates are concentrated in coal mining regions of Appalachia (Lengerich et al, 2005;. These elevated rates are partly the result of the persistent socioeconomic disadvantages that characterize coal mining areas, but even after statistical adjustment for education, poverty, smoking rates, physician supply, and other risks, some forms of cancer mortality remain elevated .…”
Section: Introductionmentioning
confidence: 99%
“…However, elevated cancer mortality rates are concentrated in coal mining regions of Appalachia (Lengerich et al, 2005;. These elevated rates are partly the result of the persistent socioeconomic disadvantages that characterize coal mining areas, but even after statistical adjustment for education, poverty, smoking rates, physician supply, and other risks, some forms of cancer mortality remain elevated .…”
Section: Introductionmentioning
confidence: 99%
“…As defined in the glossary of statistical terms by the Surveillance, Epidemiology, and End Results (SEER) program, unstaged cancer is "cancer for which there is not enough information to indicate a stage" [1], suggesting that patients with unstaged cancer have not received full diagnostic evaluation [2]. For the period 1998-2002, the percent of unstaged cases reported in SEER was 2% for breast cancer [3], 4% for prostate cancer [4], and 5% for cancer of the colon and rectum [5].…”
Section: Introductionmentioning
confidence: 99%
“…Prior research has demonstrated numerous demographic characteristics, likely associated with access to care, as being important. These studies have demonstrated that unstaged cases are disproportionately represented among patients who are older [6,9,10,11,12]; of minority descent [6,10]; with lower education [10] or history of Medicaid enrollment [6]; and those residing in Appalachian or rural areas [2]. In addition, there is variation by cancer site [10].…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologists have linked these exposures to increased risk of cardiovascular disease, 21 respiratory illnesses, 22 and cancers. 23 Because of these additional risks, the implications for pharmacists' intervention in occupational exposure go far beyond the job itself.…”
Section: Introductionmentioning
confidence: 99%
“…Epidemiologists have linked these exposures to increased risk of cardiovascular disease, 21 respiratory illnesses, 22 and cancers. 23 Because of these additional risks, the implications for pharmacists' intervention in occupational exposure go far beyond the job itself.A unique aspect of the Bill Gatton College of Pharmacy at East Tennessee State University is a component of its mission statement that emphasizes rural health care. This paper describes a case-based module created for second-(P2) and third-year (P3) doctor of pharmacy (PharmD) students at the college to help prepare them to assess patients who have suffered occupational exposure related to mining and agricultural jobs, with specific emphasis on the farming community's exposure to pesticides.…”
mentioning
confidence: 99%